Hematopoietic PBX-interacting protein mediates cartilage degeneration during the pathogenesis of osteoarthritis - Quanbo Ji; Xiaojie Xu; Lei Kang; Yameng Xu; Jingbo Xiao; Stuart B. Goodman; Xiang Zhu; Wenchao Li; Juan Liu; Xu Gao; Zhifeng Yan; Yuxuan Zheng; et al. (Nature Communications, 2019)
Osteoarthritis (OA) is associated with cartilage degeneration, and no effective therapy exists. Here, the authors show that the HPIP protein modulates OA progression by regulating Wnt signaling, and that its knockdown in joints via AAV-mediated gene silencing attentuates pathology.